2007
DOI: 10.1016/j.bbr.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among ovarian hormones and time of testing on behavioral sensitization and cocaine self-administration

Abstract: Ovarian hormones play a role in the use of drugs of abuse in women. In female rats estradiol has been shown to enhance acquisition of cocaine self-administration and behavioral sensitization induced by repeated cocaine treatment. Experiments were conducted to determine the effects of estradiol and/or progesterone on cocaine self-administration and behavioral sensitization to cocaine (10mg/kg; in animals with unilateral 6-hydroxydopamine lesions). Five groups of ovariectomized females were tested: (1) oil vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 88 publications
(139 reference statements)
5
28
0
Order By: Relevance
“…The results of the present study were not consistent with the tentatively hypothesized negative relationship between estradiol level and abstinence, which was based primarily on preclinical research suggesting estradiol may have a facilitative effect on cocaine related sensitization, self-administration and relapse/reinstatement. [51][52][53][54][55][56][57] Since there is no preclinical research examining the effects of estradiol in nicotinereinforced behavior (e.g., self-administration), the lack of association between estradiol and abstinence observed here is consistent with the possibility that estradiol may not have uniform effects across different substances of abuse.…”
Section: Discussionsupporting
confidence: 68%
“…The results of the present study were not consistent with the tentatively hypothesized negative relationship between estradiol level and abstinence, which was based primarily on preclinical research suggesting estradiol may have a facilitative effect on cocaine related sensitization, self-administration and relapse/reinstatement. [51][52][53][54][55][56][57] Since there is no preclinical research examining the effects of estradiol in nicotinereinforced behavior (e.g., self-administration), the lack of association between estradiol and abstinence observed here is consistent with the possibility that estradiol may not have uniform effects across different substances of abuse.…”
Section: Discussionsupporting
confidence: 68%
“…We have recently confirmed this finding, and shown that progesterone alone does not affect cocaine self-administration, but that progesterone enhances cocaine intake in EB primed OVX rats [141]. Taken together, a wealth of data now indicate that ovarian hormones contribute to sex differences in cocaine self-administration and that estradiol in particular is a key factor influencing the reinforcing effects of cocaine in female rats.…”
Section: Sex Differences In Stimulant Self-administration In Animalssupporting
confidence: 54%
“…However, when cocaine dose per infusion is under subject control, estrus females exhibit increased selection of higher dose and decreased selection of lower dose relative to males and females in other estrous cycle phases . Similarly, chronic estrogen treatments increase operant responding and intake of cocaine during self-administration under a variety of conditions (Hu et al 2004;Jackson et al 2006;Yang et al 2007; see however, Grimm and See 1997). It is interesting to note that when ovariectomized female rats are withdrawn from extended access to cocaine, there is a transient decline in progressive ratio responding that can be blocked by chronic estrogen treatments .…”
Section: Discussionmentioning
confidence: 96%